1976
DOI: 10.1128/jb.127.1.114-119.1976
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of histidase synthesis in intergeneric hybrids of enteric bacteria

Abstract: Regulation of the expression of the histidase coded by hutK of Klebsiella aerogenes in Salmonella typhimurium and in Escherichia coli and of the expression of the histidase coded by huts of S. typhimurium in E. coli was investigated. The hutK histidase was found to be sensitive to catabolite repression in K. aerogenes and in E. coli, but insensitive to catabolite repression in S. typhimurium; huts histidase has previously been shown to be catabolite sensitive in all three organisms. The expression of both hutK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Various studies have shown that the GS of E. coli is capable of regulating the synthesis of nitrogen-utiliing enzymes when in the cytoplasm of K. aerogenes, and that the hut operons from both S. typhimurium and K. aerogenes are regulated by GS when transferred into E. coli (7,14,30). It would seem, therefore, that the GS of E. coli possesses the ability to regulate gene expression and that E. coli has all of the necessary components for the regulation of native genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that the GS of E. coli is capable of regulating the synthesis of nitrogen-utiliing enzymes when in the cytoplasm of K. aerogenes, and that the hut operons from both S. typhimurium and K. aerogenes are regulated by GS when transferred into E. coli (7,14,30). It would seem, therefore, that the GS of E. coli possesses the ability to regulate gene expression and that E. coli has all of the necessary components for the regulation of native genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has established that the glutamine synthetase (EC 6.3.1.2) of Escherichia coli (GS5) can regulate the expression ofgenes native to KiebsieUa aerogenes (14,30). When the structural gene for glutine synthetase (glnA region) of E. coli is tansfenred into a strain of K. aerogenes lacking GS, the GSE has regulatory properties similar to that of the native GSK (30).…”
mentioning
confidence: 99%
“…In contrast, the K. aerogenes hutC gene is only slightly regulated by nitrogen conditions in E. coli [6]. In addition, there are con£icting reports regarding GDH regulation by N-availability [2,7^11], making it di¤cult to conclude if histidase and GDH are regulated in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Relief of ammonium repression. It is known that ammonium ions repress the syntheses of some nitrogen-dissimilating enzymes in E. coli (19), S. typhimurium (5), and K. aerogenes (5,19) when the cells are grown in glucose medium, and that this repression is relieved when the cells are grown with a poor nitrogen source. Catabolite repression of tyramine oxidase by glucose in K. aerogenes was relieved when tyramine was used as a nitrogen source, even in the presence of glucose (15,16).…”
Section: Resultsmentioning
confidence: 99%